Adsorptive stripping voltammetric determination of carbofuran in food using novel type of modified carbon-based electrode with grafted layers of nickel; Talanta; Vol. 267 - Solomonenko A. N. Anna Nikolaevna; Dorozhko E. V. Elena Vladimirovna; Barek J. Jiri; Korotkova E. I. Elena Ivanovna; Semin V. O. Viktor Olegovich; Erkovich A. V. Alina Vadimovna; Aseeva N. V. Natalya Valerevna (2024, 2024)
Title screen